Identification of kinematics understanding of physics students at the university in coastal area - Dwi Sundari Putri; Azhar Azhar; Rahmatina Rahim Fanny (BIO Web of Conferences, 2023)
The phenomena of kinematics are a physics concept that is close to the daily life of students. However, most students do not realize this and often ignore it. As a result, when testing their understanding of kinematics using contextual examples (cases in the coastal area), it shows that many students have low achievements. Several studies have been carried out regarding students’ understanding of kinematics. However, there is still limited identification of kinematics understanding of physics students at the university in coastal area. This study purposed to discover the conceptual understanding of the kinematics of physics students in a public university. This research was a descriptive survey that involved 129 physics students in the department of physics at Universitas Negeri Padang who tested using kinematics questions. The data obtained was analysed quantitative-descriptive. The results showed that about 26% of students have good understanding of kinematics, 6% of students have misconceptions, and 68% of students have no understanding. In conclusion, physics students still struggle to solve kinematics problems, particularly in identifying motion through a graph.